PENGARUH PENGGUNAAN EKSTRAK DAUN NIMBA (Azadirachta indica) TERHADAP POPULASI LALAT KANDANG (Stomoxys calsitrans) PADA SAPI - I Gusti Oka Wirawan; Marlin R. K. Yowi; Melkianus Ludji Djadi (Politeknik Pertanian Negeri Kupang, 2009)
An experiment was conducted to study the effect of nimba leaf extract on flies’ (Stomoxys calsitrans) population on animal house. The results were expected to be scientific basic information in developing traditional herbal medicine to control the population of fly that usually be a vector in transferring several diseases on cattle. Extract procedure refers to method developed by Kardiman (1999), the production of pesticide for crops and vegetables using spraying method. Cattle on animal house of Kupang State of Agriculture Polytechnic were arranged into three group of three. Each group of cattle, replicated three times, was sprayed with 50, 75 or 100% of nimba leaf extract. Flies’ condition and their behaviour were observed for about 3 hours. The results showed that the aplication of nimba leaf extract at concentration of 50% and 75% has no effect on flies’ activities to alight on and to suck the blood of the cattle. After 2.5 hour spraying of 100% extract, it was observed that some flies were less active, some flies almost could not fly, and the behaviour of flies change from gather together to spread out along the skin of the cattle and finally flew away from the cattle. Babes are engulfing stripper dudes cocks eag Stud enjoys playing with a large ass Joseline Kelly loves getting her teen pussy eaten and fucked Stripper gets his hard dong delighted by chick A ballet slipper wearing whore gets plowed After interview busty babe fucked Amazing redhead babe with big boobs Jessica R fucks with Latina boy Juan Largo https://www.watchfreepornsex.com/tags/xxnx-india/ Naturally beautiful brunette in fishnets gives a great erotic solo show Pornstar wannabe teen wants to be famous Teen Jesse Parker Gets Spanked Hard Horny mom Saskia is interested in the young guy in towel Leaked Amateur Russian Sextape Porn cd xx pornKeywords: nimba leaf extract, Stomoxys calsitran